Cocconeis churalis: a new marine diatom (Bacillariophyta, Cocconeidaceae) from Japan - Suzuki, Hidekazu; Nagumo, Tamotsu; Tanaka, Jiro (Phytotaxa, 2012)
A new species of Cocconeis, C. churalis, was found on a red seaweed collected from the Southwest Islands of Japan. Its morphology was examined with both light and scanning electron microscopy and the details are described here. This small diatom is characterized by the concave raphid valve with a slightly sigmoid raphe and uniseriate striae consists of circular areolae occluded by hymenes with perforations arranged in centric array type, the convex araphid valve with uniseriate striae consists of several alveoli occluded hymenes with perforations arranged in a parallel array type, and the cingulum consists of four non-fimbriated girdle bands including a valvocopula.